2000
DOI: 10.1086/308782
|View full text |Cite
|
Sign up to set email alerts
|

Near‐ and Mid‐Infrared Subarcsecond Structure of the Dusty Symbiotic Star R Aquarii

Abstract: The results of a high-resolution interferometric campaign targeting the symbiotic long-period variable (LPV) R Aqr are reported. With both near-infrared measurements on baselines out to 10 m and midinfrared data extending to 32 m, we have been able to measure the characteristic sizes of regions from the photosphere of the LPV and its extended molecular atmosphere out to the cooler circumstellar dust shell. The near-infrared data were taken using aperture-masking interferometry on the Keck I telescope and show … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 37 publications
(52 reference statements)
3
41
0
Order By: Relevance
“…However, it cannot be ruled out that the uncertainties in the adopted optical properties may result in the low temperatures. Recent interferometric observations have suggested that the inner dust shell is located at the region with temperatures around 1000 K for o Cet and 850 K to 1170 K for R Aqr although the infrared spectrum from the fitted models did not show a satisfactory agreement with the observed spectra (Danchi et al 1994;Tuthill et al 2000). Episodic mass loss in AGB stars has been suggested by several observations (Izumiura et al 1997;Hashimoto et al 1998) and it could also lead to low inner dust shell temperatures.…”
Section: Introductionmentioning
confidence: 93%
“…However, it cannot be ruled out that the uncertainties in the adopted optical properties may result in the low temperatures. Recent interferometric observations have suggested that the inner dust shell is located at the region with temperatures around 1000 K for o Cet and 850 K to 1170 K for R Aqr although the infrared spectrum from the fitted models did not show a satisfactory agreement with the observed spectra (Danchi et al 1994;Tuthill et al 2000). Episodic mass loss in AGB stars has been suggested by several observations (Izumiura et al 1997;Hashimoto et al 1998) and it could also lead to low inner dust shell temperatures.…”
Section: Introductionmentioning
confidence: 93%
“…Perrin et al 1999;Weigelt et al 2002) or in the baseline dependence of UD fit diameters, and in the bandpass-dependence of near-continuum UD fit diameters (e.g. Tuthill et al 2000;Mennesson et al 2002b;Thompson et al 2002; conference reports listed in JS02).…”
Section: Spectral Indications Of Visibility Distortionsmentioning
confidence: 99%
“…therein). In spite of the long history of study using the largest telescopes (Keck I: Tuthill et al 2001;MMT: Karovska et al 1994;VLA, BIMA, VLBA: Hollis et al 2000, its nature and physical parameters remain unclear and sometimes controversial. Tuthill et al (2001), in contrast to the conclusions of Karovska et al (1994), do not find evidence of elongation of the CS envelope along position angle θ ≈ 140…”
Section: R Aqr: An Unusual Symbiotic Starmentioning
confidence: 99%
“…In addition, no evidence for the presence of a companion separated by more than ∼15 mas was found by them, but a significant deviation from circular symmetry of the CS dust envelope was reported. Hollis et al (2001) reported that the axis of rotational Season θU /σ θB/σ θV /σ θR C /σ θI C /σ 1994 131 Tuthill et al (2001) stressed the importance of polarimetric measurements to determine the optical properties of the dust.…”
Section: And Referencesmentioning
confidence: 99%